2018
DOI: 10.1093/mmy/myy112
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides brasiliensis 14-3-3 protein is important for virulence in a murine model

Abstract: The Paracoccidioides brasiliensis strain downregulated the expression of adhesin Pb14-3-3 (Pb14-3-3 aRNA) was evaluated in a murine model of paracoccidioidomycosis (PCM). Pb14-3-3 aRNA displays attenuated virulence and triggered the formation of fewer granulomas by lowering the fungal burden in the lungs. Additionally, the Pb14-3-3 aRNA showed more elongated yeast cells and less ability to induce pneumocytes apoptosis in vitro. Our results show that 14-3-3 is an important virulence factor in P. brasiliensis-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The downregulation of Pb14-3-3 leads to morphological modifications, such as more elongated cells, an impairment in dimor-phism, decreased interaction with pneumocytes, and reduced bud number [101]. Still, in P. brasiliensis, Marcos et al [102] observed that the downregulation of the 14-3-3 protein alters the pathogen's ability to cause host cell apoptosis, which may be due to a consequence of the decreased secretion of Pb14-3-3 or the loss of putative adherence mediated by 14-3-3. In Pythium insidiosum, this protein may be related to the pathogen's virulence favoring the adhesion process, as mentioned in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The downregulation of Pb14-3-3 leads to morphological modifications, such as more elongated cells, an impairment in dimor-phism, decreased interaction with pneumocytes, and reduced bud number [101]. Still, in P. brasiliensis, Marcos et al [102] observed that the downregulation of the 14-3-3 protein alters the pathogen's ability to cause host cell apoptosis, which may be due to a consequence of the decreased secretion of Pb14-3-3 or the loss of putative adherence mediated by 14-3-3. In Pythium insidiosum, this protein may be related to the pathogen's virulence favoring the adhesion process, as mentioned in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…These antigens have already been demonstrated to be crucial in the pathogenesis and virulence of several fungi, such as Histoplasma capsulatum [63,64], Paracoccidioides spp. [61,65,75,76,80,100,102], Aspergillus fumigatus [84], Saccharomyces cerevisiae [60,82,89], Cryptococcus neoformans [79,90], and Candida albicans [83]; as well as in studies involving the development of vaccines for Candida albicans [77,78] and Paracoccidioides spp. [103].…”
Section: Discussionmentioning
confidence: 99%
“…The 14-3-3 protein is an important virulence factor of Paracoccidioides spp. acting as an essential adhesin [17][18][19]. Therefore, we aimed to determine candidates of immunogenic peptides from this protein and evaluate their biological activity and immunogenic potential in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the S. cerevisiae strain showed increased expression of genes in the ergosterol pathway, the target for azoles [17]. Marcos et al [18,19], using a 14-3-3-silenced strain of P. brasiliensis, demonstrated that in vitro 14-3-3 is important to the interaction with pneumocytes, and in vivo, showed less virulence in both G. mellonella and murine models, causing low granuloma and fungal burden in the last model. In this way, 14-3-3 protein is considered an important virulence factor of Paracoccidioides spp.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific community looks forward to seeing the CRISPR/CAS9 system, which is widely used for functional study of genes in fungal kingdom members, being applied to Paracoccidioides shortly. Even with this delay in the development of appropriate molecular tools compared to other human pathogenic fungi, several studies have been published in the past few years, using the gene expression modulation approach described by Almeida et al [51][52][53][54][55][56][57][58][59][60].…”
Section: From the First Description Of The Disease To Functional Genomics-112 Years Of Gathered Knowledge A Brazilian Middle West Perspecmentioning
confidence: 99%